PELATIHAN KETERAMPILAN BERBICARA BAHASA INGGRIS DENGAN METODE STORYTELLING DI SMAK KASIH ANUGERAH - Pramusita, Santa Maya; Situmorang, Komilie; Arkianti, Maria Maxmilla Yoche; Rumambi, Magda Fiske (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
English is not commonly utilized for daily communication in Indonesia due to its status as a foreign language. Consequently, it is common for a significant number of Indonesian students to lack sufficient proficiency in spoken English. The same applies to pupils at SMAK Kasih Anugerah, Bojong Nangka, Tangerang. Furthermore, a significant number of pupils experience apprehension when required to communicate in English. In response to this issue, the English team at UPH Faculty of Nursing has made the decision to conduct an intensive one-month English speaking training program for students at SMAK Kasih Anugerah. The methodology employed is Communicative Language Teaching (CLT), more especially utilizing the storytelling technique. The selection of this method was based on its numerous advantages in fostering the enhancement of students' English speaking abilities and its capacity to cultivate an enjoyable and engaging learning environment. The first three weeks focused on the study and practice of storytelling materials and strategies. During the previous week, a storytelling competition took place, providing students with an opportunity to apply the theoretical knowledge they had acquired. The evaluation results indicated that the majority of students had confidence in their ability to narrate stories in English, as well as exhibited proficient and accurate pronunciation of vocabulary. All students on the evaluation sheet expressed contentment with the training and voiced a desire for a subsequent session. Additionally, they asserted that their proficiency in vocabulary significantly enhanced as a result of reading numerous story texts provided by the facilitators.